Pengaruh Pendidikan Terhadap Anemia pada Ibu Hamil di Kabupaten Pemalang - Kurniati, Ade; Rini, Urip Sertiyo (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
Maternal mortality in Indonesia is still high, including Central Java in 2015 Maternal mortality rate of 111.16 / 100,000 live births. Kabupaten Pemalang in 2016 was ranked second of maternal deaths in Central Java. The indirect cause of maternal mortality is anemia of pregnancy. This study aims to analyze the effect of education on anemia in pregnant. The research design used observational analytic with cross sectional approach.Â  The population used is pregnant who are in Puskesmas Rowosari, Purwoharjo dan Petarukan. The sampling technique used Fixed Disease Sampling with a total sample of 146 pregnant women. Analysis data used chi square. The results that respondents who experienced anemia tend to have low education that is 74 people (67,5%), while high educated 14 people (20,5%). Respondents who not anemia with low education 38 people (44,5%), while the highly educated 20 people (13.5%). It is concluded that there is correlation of education influence to anemia in pregnant mother in Kabupaten Pemalang with p-value = 0,016 < Î± (0,05). Pregnant are expected to increase interaction with midwives because it will increase knowledge about anemia.Keyword; Anemia, Pregnant, Education, Maternal Morality